TINGKAT KEPUASAN BIMBINGAN KLINIK MAHASISWA KEPERAWATAN - Linda Khilyatul Azizah; Chandra Bagus Ropyanto (Jurnal Keperawatan Diponegoro, 2012)
Clinical supervision plays a significant role in professional nursing education. The quality of clinical supervision is affected by the students’ satisfaction level towards its process. A qualitative research about satisfaction level of clinical supervision showed that nursing students who was dissatisfied with their clinical field did not brave to give nursing assessment in the clinical setting. This research’s purpose is to identify clinical supervision’s satisfaction level of nursing students. This research represented qualitative design with cross sectional approach and was done at Nursing Science Program Faculty of Medicine Diponegoro University with 57 respondents. The result of the students’ satisfaction level showed that 34 respondents (59,6%) were satisfied with the clinical supervision and 23 respondents (40,4%) were dissatisfied. To sum up, the research showed that most of nursing students were satisfaied with clinical supervision. The quality of clinical supervision will be increased if professional nursing institution and clinical institution collaborate to make a legal role about its process, besides they have to evaluate the growth of clinical supervision continuously